AVALIAÇÃO DE DICIONÁRIOS: UMA PROPOSTA METODOLÓGICA - Faulstich, Enilde (Organon, 2011)
This text presents a methodological proposal to the evaluation of dictionaries ofdifferent types. We consider the evaluation procedures to be satisfactory enough in thatdictionaries are richly informative reference works which require accurate reading. Having thisin mind we made up a form with content details which usually are not met in dictionaries. Tothis end, we studied the macrostructure and the microstructure of some large dictionaries as thestarting point to create guidelines in a record format. This study started at Lexterm Center in1995 and continuous evaluations allowed us to improve it. Though not regarded as a definitivemodel, we recognized the proposal validity considering the number of works already analyzed;